DAMPAK PERCERAIAN ORANG TUA BAGI PSIKOLOGIS ANAK (STUDI KASUS DI DESA WONOREJO KECAMATAN BANYUPUTIH KABUPATEN SITUBONDO) - Heriberthus Wicaksono; Toni Arya Saputra; Ahmad Sulthoni (Program Studi Bimbingan dan Konseling, 2022)
This study aims to determine the impact of parental divorce on child psychology. The method used is qualitative research with a case study approach. The subjects in this study were one 10-year-old child with two key informants who live in Wonorejo Village, Banyuputih District, Situbondo Regency. The results of this study indicate that divorced parents will have a psychological impact on children, including children who receive less attention, protection, and affection from their father and mother. The impact of parental divorce on children's psychology in Wonorejo Village, Banyuputih District, Situbondo Regency, has several impacts. The impacts that researchers get are shame and sadness due to a disorganized family. Meanwhile, the positive impact of parental divorce on children's psychology in Wonorejo Village, Banyuputih District, Situbondo Regency is in the form of children becoming more independent and having solutions in the ability to survive.